The Rapid Social Immersive Learning (RaSIL) framework: bridging the gap for MSW students without prior formal social work training. - Odathakkal, Jolly John; Thadathilparambil Rajan, Rajeemol; Roy, Roal; Thampi, Kiran; Mannooparambil Kuncheria, Joseph (Social Work Education, 2026)
The Rapid Social Immersive Learning (RaSIL) framework is an innovative pedagogical intervention aimed at rapidly fostering critical competencies in social work students with no prior formal social work training. The RaSIL framework integrates experiential learning through intensive 12-hour immersive fieldwork, enabling students to engage directly with marginalized communities and confront real-world social challenges. Grounded in Kolb's theory of experiential learning, the framework emphasizes the development of compassion, social intelligence, and professional readiness in a compressed time frame. The study employed a single-arm pre-post design to assess the impact of the RaSIL framework on 37 first-year Master of Social Work (MSW) students in India. Social intelligence and compassion were measured using the Tromso Social Intelligence Scale (TSIS) and Compassion Scale (CS) before and after the intervention. Results demonstrated significant improvements in social intelligence and compassion scores, with multiple regression analyses highlighting key socio-demographic factors influencing these outcomes. The findings suggest that the RaSIL Framework can effectively cultivate essential competencies in social work students, contributing to their professional development within a constrained educational timeframe. This study offers valuable insights for educators and policymakers seeking to innovate social work education through experiential and immersive approaches.